2014
DOI: 10.1002/ajhb.22561
|View full text |Cite
|
Sign up to set email alerts
|

Is there an influence of modern life style on skeletal build?

Abstract: The present investigation confirms the decline in relative elbow breadth in recent decades. Analogue, but even more pronounced changes were detected in pelvic breadth that coincides with the modern decline in upright locomotion. The findings underscore the phenotypic plasticity of humans while adapting to new environmental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
(45 reference statements)
0
26
0
5
Order By: Relevance
“…As a parallel trend to the increase in overweight and obesity, a decline in external skeletal robusticity in school children and young adolescents was observed in the last 20 years, e.g. in Germany (Scheffler 2011;Rietsch et al 2013a;Scheffler & Hermanussen 2014) and Russia (Rietsch et al 2013b). As a main reason lack of activity, in particular daily physical activity, is assumed (Rietsch et al 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…As a parallel trend to the increase in overweight and obesity, a decline in external skeletal robusticity in school children and young adolescents was observed in the last 20 years, e.g. in Germany (Scheffler 2011;Rietsch et al 2013a;Scheffler & Hermanussen 2014) and Russia (Rietsch et al 2013b). As a main reason lack of activity, in particular daily physical activity, is assumed (Rietsch et al 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…The percentage of body fat also increased in normal‐weight children and adolescents over time. Intriguingly, skeleton breadth measures taken from the same population decreased over time (Scheffler & Hermanussen, ). Together our results and the previous study demonstrate that normal‐weight individuals of one population had a lower percentage of body fat and more bones and muscles in 1982–1991 as compared to the years 1997–2012.…”
Section: Discussionmentioning
confidence: 99%
“…But this decrease of physical activity is a Germany‐wide and worldwide phenomenon (Sandercock, Voss, McConnell, & Rayner, ; Sigmundová, El Ansari, Sigmund, & Frömel, ). Recent research has extensively addressed whether and how changes in physical activity (Woll et al, ; Walther, Kramer, & Röbl, ; Müller, Koertzinger, Mast, Langnäse, & Grund, ) and nutrition contribute to the increasing rate of obesity (Kromeyer‐Hauschild, 2012) and even lead to alteration of body composition (Rietsch, Eccard, & Scheffler, ; Scheffler & Hermanussen, ) in the German population.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the Frame‐Index in children has a positive relationship with not only BMI but also BF% and stronger with physical activity (PA) (Rietsch, Eccard, & Scheffler, ). Therefore, an important body of research indicates that skeletal morphology in childhood is strongly related to the modern lifestyle (Hermanussen, Scheffler, Groth, & Aßmann, ; Scheffler & Hermanussen, ) and that it can change according to the characteristics of each locality (Mumm et al, ; Rietsch, Godina, & Scheffler, ).…”
Section: Introductionmentioning
confidence: 99%